KAJIAN ARAH PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH KABUPATEN KULON PROGO - , ROMADHONI WULANDARI; , Dodi Widiyanto, S.Si., MRegDev ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Micro, small, and medium enterprises or SMEs in Indonesia each year has increased. The increasing number of SMEs needs to be assisted in order to achieve the firm, independent, and high grade so be able to solve the problems based on confidence and capability of units. The purpose of this study is to know the characteristic of SMEs, to determine the potential leading sector and the location of leading sector, and to determine the most appropriate development policy. Collecting data uses secondary data and in depth interview to the relevant parties. Analysis technique is using descriptive analysis technique and data processing uses LQ and SWOT strategy. The result are 1) The characteristic of SMEs are i) The highest sum of unit, ii) The highest sum of labour, iii) The highest cost of used energy